Socioeconomic status and improvement in functional ability among older adults in Japan: a longitudinal study - Airi Amemiya; Naoki Kondo; Junko Saito; Masashige Saito; Daisuke Takagi; Maho Haseda; Yukako Tani; Katsunori Kondo (BMC, 2019)
Abstract Background Recovery from functionally disabled status is an important target of public health measures for older adults. This study aimed to examine socioeconomic inequalities in the improvement of functional ability among older adults stratified by the level of disability at baseline. Methods In the Japan Gerontological Evaluation Study, we conducted a mail survey of community-dwelling older adults (1937 men and 2212 women) who developed functional impairment during 2010-2014. The survey data were individually linked to the longitudinal records of changes in the levels of functional disability based on the Public Long-Term Care Insurance System. Results The mean (standard deviation) follow-up period was 316 (269) days. During follow-up, 811 participants (19.5%) showed improved functional ability. Among those with severe disabilities at baseline, men with 13 or more years of education were more likely to improve functional ability than men with 9 or fewer years of education (hazard ratio: 1.97, 95% confidence interval: 1.12-3.45). A similar association was observed among women (hazard ratio: 2.16, 95% confidence interval: 1.03-4.53). Neither income nor occupation was statistically associated with improved functional ability. Conclusions There are education-related inequalities in the improvement of functional ability, especially among older adults with severe disabilities. Health policy makers and practitioners should consider the educational background of individuals with reduced functionality in formulating strategies to improve their functional ability.